Different planting dates of soybean intercropping for Striga (Striga hermonthica Del Benth) control and sorghum productivity, Northwest Ethiopia - Zenebe Gebremedhin (Cogent Food & Agriculture, 2021)
Striga hermonthica is a major biotic threat to worldwide food security, especially in sub-Saharan Africa. Sorghum production in North Gondar is challenged by the parasitic weed causing low crop yields. One of the options widely practiced is intercropping with legumes and variation in sowing dates of the intercropped crop species. A field experiment was conducted at two locations; Metema and Sanja at Gondar Agricultural Research Centers in the 2017/18 cropping season. Three sowing dates of soybean (2 weeks and 1 week before sowing and at a sorghum plantation) to control Striga. The study laid in a randomized complete block design with three replications in a factorial combination, two sorghum varieties; improved (Berhan) and a local variety commonly grown in the area and soybean “Afgat” varieties were used. A highly significant difference between Striga count (SC) and dry matter, grain yield (GY), above-ground biomass, and thousand seed weight (TSW) were the main effects and their interactions. SC, GY, and TSW were significant at Metema and combined over locations, but only GY at Sanja. Highest grain yield, biomass, thousand seed weight and lowest Striga counts was obtained in resistant variety at 2 weeks soybean sown before sorghum and, highest Striga was recorded in susceptible variety where soybean was sown at the same date with sorghum. Economic analysis results showed the highest and lowest net returns of 32,048.50 and 8,660 ETB per hectare from 2 weeks before with resistant sorghum and the same date with susceptible sorghum, respectively. Therefore, in the study area, the “Berhan” variety at 2 weeks before sorghum sowing is recommended for profitable sorghum production and Striga management.